Application of the Project Based Learning Model Assisted by the Learningapps Application on Student Learning Outcomes in Class IX - Muhammad Raihan Zaki; Suprih Widodo; Nuur Wachid Abdul Majid (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The use of learning models and technological assistance in class greatly influences student learning outcomes in ICT subjects. This can be seen from the results of a preliminary study conducted on class IX students at MTs Assalam where learning outcomes in ICT subjects were still lacking. The purpose of this study was to apply the Project Based Learning model assisted by the Learningapps application in IX class IX students at MTs Assalam and improve student learning outcomes. This study used classroom action research with 2 cycles of stages and 30 students as research subjects. The results of the research show that the application of the Project Based Learning model assisted by the Learningapps application can improve the learning outcomes of class IX students at MTs Assalam in ICT subjects. Improved student learning outcomes can be seen based on the results of activities in class, the results of individual tests, as well as the results of group projects. Based on the results of student activities, it was seen that there was an increase from initially obtaining 70% in cycle I to 78% in cycle II. Furthermore, on individual tests, it was found that in cycle I, the class average was 73 with a passing percentage of 67% and an N-Gain score of 70.9. Then in cycle II, obtaining a class average of 86 with a passing percentage of 90% and an N-Gain value of 84.4. Finally, in group projects, it is also known that there is an increase which can be seen from the initial average of 72 in cycle I with a completeness percentage of 63% to an average of 85 in cycle II with a completeness percentage of 100%.